Relationship among service accessibility, social norms, herpes zoster vaccination intention of middle-aged and older adults in Chongqing: mediating role of perceived usefulness - Deng, Yanxi; Wang, Tianran; Yu, Li; Fu, Xin; Luo, Yaman; Chen, Fei (Frontiers in Public Health, 2025)
ObjectiveThe study aims to explore the relationship of vaccination service accessibility, social norms, and perceived usefulness on the intention to get the herpes zoster vaccine (HZV) among middle-aged and older adults, and to provide suggestions for promoting the health and disease prevention of this population.MethodsA questionnaire was developed based on the Stimulus-Organism-Response (SOR) theory. Utilizing stratified random and convenience sampling, the study enrolled participants aged 45 years and above. A structural equation modeling approach was employed to explore the relationships among external factors, perceived usefulness and vaccination intention among the surveyed population.ResultsUltimately, a datasets consisting of 481 valid samples was obtained. Social norms and perceived usefulness were positively associated with the intentions of middle-aged and older adults to receive HZV. Accessibility of vaccination services and social norms were also positively related to perceived usefulness, while accessibility showed no direct correlation with vaccination intention. Perceived usefulness was found to mediate the relationships between both accessibility and social norms with vaccination intention.ConclusionSocial norms and perceived usefulness are significant associated with vaccination intentions. Both vaccination services and social norms were related to vaccination intention through the mediation of perceived usefulness. This study emphasizes the role of perception in external information and willingness to vaccinate. Vaccination management should be strengthened to enhance service accessibility and reduce economic burdens. Promote a social consensus on vaccination to prevent disease. Attention to social norm contents and official channels, coupled with increased perceived usefulness, can further bolster vaccination intentions among adults aged 45 and above.